2018
DOI: 10.1080/00220388.2018.1464148
|View full text |Cite
|
Sign up to set email alerts
|

External Social Ties and Loan Repayment of Group Lending Members: A Case Study of Pro Mujer Mexico

Abstract: We investigate how external social ties, that is, social ties with individuals outside the borrowing group, determine loan repayments of individual borrowers in joint liability group lending. We measure the resources in external ties in terms of the informal risk insurance arrangement they embed. The ties borrowers have with individuals outside the group and the informal risk insurance arrangement they represent, help to survive in general, and repay their loans in particular. The risk of losing these ties inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…β=0.170, p≤0.05). The study therefore rejected the null hypothesis and accepted the alternate hypothesis which showed that there was a relationship between financial knowledge and skills and financial sustainability of affirmative groups.The study findings concur with study done by Postelnicu, Hermes, and Servin (2019) examined external social ties and loan repayment of group lending members of Pro Mujer in Mexico.…”
Section: Page 3139supporting
confidence: 91%
See 1 more Smart Citation
“…β=0.170, p≤0.05). The study therefore rejected the null hypothesis and accepted the alternate hypothesis which showed that there was a relationship between financial knowledge and skills and financial sustainability of affirmative groups.The study findings concur with study done by Postelnicu, Hermes, and Servin (2019) examined external social ties and loan repayment of group lending members of Pro Mujer in Mexico.…”
Section: Page 3139supporting
confidence: 91%
“…The researchers found that financial knowledge had a significant effect on financial sustainability of affirmative groups in Ethiopia. Postelnicu, Hermes, and Servin (2019) examined external social ties and loan repayment of group lending members of Pro Mujer in Mexico. The study aimed at establishing whether external social ties had effect on loan repayment.…”
Section: Financial Knowledge and Skills And Financial Sustainability Of Affirmative Groupsmentioning
confidence: 99%
“…This dimension relates to the social capital view arguing that cross-country variations in interpersonal and institutional trust influences perceptions on the likelihood or ability of counter parties in business to act opportunistically (Dowling et al, 2019). For example, Postelnicu et al (2019) conclude that the risk of losing external social ties increases the willingness to repay loans, suggesting that such ties could serve as a substitute for collateral. Furthermore, high levels of bridging capital facilitate the smooth function of the economy as they represent the level of trust required for institutions and legal systems to prosper (Legatum Institute, 2017).…”
mentioning
confidence: 99%
“…should be associated with higher repayment efficacy. JLL groups with the opportunity for indirect reciprocity, such as when members share mutual acquaintances within a larger social network (Postelnicu et al, 2019), or engage in many social activities outside the group, should have higher repayment efficacy as this may provide a means to acquire and spread reputational information.…”
Section: Prior Interactionmentioning
confidence: 99%